A Study Of Global Warming In Malaysia - Ng Meng, Wai; Alejandro, Camerlengo; Abdul Wahab, Ahmad Khairi (Penerbit UTM Press, 2005)

(untitled)
The Aim Of This Investigation Is To Study The Global Warming Trend In Malaysia. This Investigation Uses Approximately 50 Years Of Temperature Data Set. Least Square Regression Line, Coupled With Null Hypothesis Tests Were Carried Out To Detect Any Significant Trend. The Most Significant Results Of This Investigation Are: (A) A Significant Increase Of The Mean Annual Temperature, Ranging From 0.99 To 3.44Â°C Per 100 Years Is Forecasted, And (B) The Mean Annual Temperature Regression Lines (For All The Analyzed Stations) Exhibit That The Global Warming Trend Has Increased In The Past 30 Years. This Last Result Shows A Perfect Agreement With The Latest Report Of The Intergovernmental Panel Of Climatic Change (IPCC).